Another blooming ACP winner - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Kenya has taken over the top slot in global flower exports: exports in 2001 were up to 32 million kg of flowers by early October, compared with 38.2 million kg in the whole of 2000.Competitors countries have suffered their setbacks: Latin American...